Electron Donor-Acceptor Capacity of Selected Pharmaceuticals against COVID-19 - Ana Martínez (MDPI AG, 2021)
More than a year ago, the first case of infection by a new coronavirus was identified, which subsequently produced a pandemic causing human deaths throughout the world. Much research has been published on this virus, and discoveries indicate that oxidative stress contributes to the possibility of getting sick from the new SARS-CoV-2. It follows that free radical scavengers may be useful for the treatment of coronavirus 19 disease (COVID-19). This report investigates the antioxidant properties of nine antivirals, two anticancer molecules, one antibiotic, one antioxidant found in orange juice (Hesperidin), one anthelmintic and one antiparasitic (Ivermectin). A molecule that is apt for scavenging free radicals can be either an electron donor or electron acceptor. The results I present here show Valrubicin as the best electron acceptor (an anticancer drug with three F atoms in its structure) and elbasvir as the best electron donor (antiviral for chronic hepatitis C). Most antiviral drugs are good electron donors, meaning that they are molecules capable of reduzing other molecules. Ivermectin and Molnupiravir are two powerful COVID-19 drugs that are not good electron acceptors, and the fact that they are not as effective oxidants as other molecules may be an advantage. Electron acceptor molecules oxidize other molecules and affect the conditions necessary for viral infection, such as the replication and spread of the virus, but they may also oxidize molecules that are essential for life. This means that the weapons used to defend us from COVID-19 may also harm us. This study posits the idea that oxide reduction balance may help explain the toxicity or efficacy of these drugs. These results represent a further advance on the road towards understanding the action mechanisms of drugs used as possible treatments for COVID-19. Looking ahead, clinical studies are needed to define the importance of antioxidants in treating COVID-19.